Analysis of properties and counting of orbits for k-rotation symmetric Boolean functions - Quan LI; Guang-pu GAO; Wen-fen LIU (Tongxin xuebao)
The properties of k-rotation symmetric Boolean functions (k-RSBF) were analyzed.It was presented that the Walsh spectrum and auto-correlation value were invariant when the parameters of a k-rotation symmetric Boolean function were under k-circular translation of indices were presented.The analysis of the properties showed that many properties of k-RSBF could be described by their orbits,and the counting formulas of long cycles and short cycles on k-RSBF’ orbits were given.